Synthesis and Preclinical Evaluation of Urea-Based Prostate-Specific Membrane Antigen-Targeted Conjugates Labeled with 177Lu; ACS Pharmacology & Translational Science; Vol. 7, iss. 5 - Machulkin A. E. Aleksei; Petrov S. A. Stanislav Aleksandrovich; Bodenko V. V. Vitalina Vasiljevna; Larkina M. S. Mariya Sergeevna; Plotnikov E. V. Evgeny Vladimirovich; Yuldasheva F. Sh. Feruza Sherzod kizi; Tretyakova (Tretjyakova) M. S. Maria Sergeevna; Bezverkhniaia E. A. Ekaterina Aleksandrovna; Zyk N. Yu. Nikolai; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Mazhuga A. G. Aleksandr Georgievich; et al. (2024, 2024)
Title screen